CLINICAL AND PHYSIOLOGICAL ACTIVITY OF «NUTRILON 1 WITH PREBIOTICS IMMUNOFORTIS» COMPOUND (2 YEAR FOLLOW UP) - T.G. Reshetova; N.G. Sokolova; E.A. Anikieva ("Paediatrician" Publishers LLC, 2008)
Clinical and physiological activity of «Nutrilon 1 with prebiotics immunofortis» compound in children of first year of life was analyzed. This compound has prolonged prebiotic and immunomodulatory activity. Key words: children of first year of life, nutrition, prebiotics.